(untitled) (Bangladesh Journal of Child Health, 2012)
Background: Meningitis in children constitutes a formidable illness worldwide due to its high morbidity and mortality. The etiological agents and other associated epidemiological factors contributing to its occurrence and prognosis varies from place to place. Identification of these factors is crucial for the reduction of this important health problem. This record-based observational study was conducted in Medical College & Hospital, Kolkata, India to identify the socio-demographic profiles, etiological types and nutritional status of the meningitis cases admitted in the Pediatric Medicine department in this institute during the last three years and to find out the duration of hospital stay, case fatality rates and seasonal variations in different etiological types of the disease. Materials and Method: This observational record based study was conducted in Medical College & Hospital, Kolkata, a tertiary care hospital located in central area of the city of Kolkata, India. It provides health care services to the urban population as well as rural population of different districts of the state of West Bengal, and also to population from outside of the state. The available records of all the meningitis cases admitted in pediatric medicine department of the Institution from January 2007 to December 2009 were studied. The variables included were age, sex, religion, residence, nutritional status, etiological type of meningitis, duration of hospital stay, case fatality rate (CFR) and seasonal variation. The collected data were analyzed with suitable statistical methods. Results: A total of 326 meningitis cases in the age group below twelve years comprised the study population. More than 27% of the cases were infants and about 44% were below three years of age. The majority of the cases were male (60.43%), Hindu (64.42%) by religion and rural (74.23%) by residence. Fifty seven percent of the cases were tuberculous and 34.66% were pyogenic by etiological type. Among those who survived (224) the overall prevalence of undernutrition was 66.52% with a significantly higher proportion of undernutrition observed in tuberculous meningitis (75.59%) compared to that among pyogenic meningitis (54.16%). For 59.06% of tuberculous and 57.32% of pyogenic cases the hospital stay was between 1-2 weeks. The overall case fatality rate (CFR) was 31.29%. Compared to viral meningitis, the CFR was significantly higher both in pyogenic and tuberculous meningitis. Some seasonal variation was also observed with two peaks in case of pyogenic and four peaks in case of tuberculous meningitis. Conclusion: It can be concluded that case fatality rate was quite high in pyogenic and tuberculous meningitis even in this era of modern medicine. Higher proportion of patients from rural locations and a high prevalence of undernutrition among the cases point to socio-economic aspects of the disease. DOI: http://dx.doi.org/10.3329/bjch.v36i1.13031 Bangladesh J Child Health 2012; Vol 36 (1): 20-25